A randomised controlled trial comparing deep neuromuscular blockade reversed with sugammadex with moderate neuromuscular block reversed with neostigmine. (12th May 2020) - Boggett, S.; Chahal, R.; Griffiths, J.; Lin, J.; Wang, D.; Williams, Z.; Riedel, B.; Bowyer, A.; Royse, A.; Royse, C.
Summary: Deep neuromuscular block aims to improve operative conditions during laparoscopic surgery with a lower intra‐abdominal pressure. Studies are conflicting on whether meaningful improvements in quality of recovery occur beyond emergence, and whether lower intra‐abdominal pressure is achieved. In this pragmatic randomised trial with 1:1 allocation, adults undergoing elective laparoscopic surgery were allocated to moderate neuromuscular block reversed with neostigmine, or deep neuromuscular block reversed with sugammadex. Allocation was revealed to the anaesthetist only. Primary outcome was cognitive recovery of the Postoperative Quality of Recovery Scale, 7 days after surgery. Secondary outcomes included recovery in other domains of the Postoperative Quality of Recovery Scale at 15 min and 40 min; days 1, 3, 7, 14; and 1 and 3 months after surgery. Chi‐square test was used for the primary outcome, and generalised linear mixed model for recovery over time between groups. Of 350 participants randomised, 140 (deep) and 144 (moderate) were analysed for the primary outcome. There was no difference in the Postoperative Quality of Recovery Scale cognitive domain at day 7 (deep 92.9% vs. moderate 91.8%, OR 1.164; 95%CI 0.486–2.788, p = 0.826), or at any other time‐point. No significant difference was observed for physiological, emotive, activities of daily living, nociception, or overall recovery. Length of stay in the recovery area (mean (SD) deep 108 (58) vs. moderate 109 (57) min, p = 0.78) and hospital (1.8 (1.9) vs. 2.6 (3.5) days, p = 0.019) was not different. Intra‐abdominal pressure and surgical operating conditions were not different between groups. Deep neuromuscular block did not improve quality of recovery compared with moderate neuromuscular block in operative laparoscopic surgery over a 1‐h duration.